The Use of NMR to Study Transient Carbohydrate—Protein Interactions - Nieto, Pedro M. (Frontiers in Molecular Biosciences, 2018)
Carbohydrates are biologically ubiquitous and are essential to the existence of all known living organisms. Although they are better known for their role as energy sources (glucose/glycogen or starch) or structural elements (chitin or cellulose), carbohydrates also participate in the recognition events of molecular recognition processes. Such interactions with other biomolecules (nucleic acids, proteins, and lipids) are fundamental to life and disease. This review focuses on the application of NMR methods to understand at the atomic level the mechanisms by which sugar molecules can be recognized by proteins to form complexes, creating new entities with different properties to those of the individual component molecules. These processes have recently gained attention as new techniques have been developed, while at the same time old techniques have been reinvented and adapted to address newer emerging problems.